Hubungan Dukungan Suami, Tingkat Kecemasan, Dan Pijat Endorphine Terhadap Nyeri Persalinan Pada Ibu Bersalin Kala 1 Fase Aktif - Eva Sunasty; Ageng Septa Rini; Astrid Novita (STIKes Santa Elisabeth Medan, 2023)
Murray reported that in Indonesia the incidence of labor pain in 2,700 mothers giving birth was only 15% of labor that took place with mild pain, 35% with moderate pain, 30% with severe pain and 20% of labor with very severe pain. The purpose of this study was to find out the relationship between husband's support, anxiety, endorphin on the level of labor pain in active phase 1 labor mothers at PMB E Jakarta in 2022. Method used quantitative research with analytic descriptive research and used a cross sectional design. The sample in 30 mothers giving birth in the active phase of the first stage. Data analysis Chi-square test. Results Husband support P-Value of 0.003 and OR of 2.112, Anxiety P-Value of 0.004 and OR of 1.889. And Endorpine P-Value of 0.000 and an OR of 7.259. Concluded that there is a relationship between Husband's Support, Anxiety ,Endorphine and labor pain at PMB Midwife E in 2022, where statistical results obtained P-Value < α (0.05). Suggestion Midwives are expected to be able to use endorphin massage therapy for mothers in labor to reduce pain during labor and midwives advise husbands to follow mothers in the delivery room so that mothers get support in order to reduce anxiety and make classes pregnant women and husbands are taught to do Endorpine massage.